Statistical Assessment of the Effectiveness of Public Capital Investments in the Development of Ukraine’s Regions - Gerasymenko, S. S.; Horna, М. O.; Ivanenko, D. V. (Statistics of Ukraine, 2025)
This article analyzes statistical approaches to evaluating the effectiveness of state capital investments in the context of socio-economic development in Ukrainian regions. It identifies the need for a quantitative analysis of the relationship between budgetary allocations and key regional development indicators: gross regional product, employment levels, entrepreneurial activity, export openness, and environmental status. To ensure the reliability and validity of the conclusions, various statistical methods were applied, including descriptive statistics, data normalization, linear correlation analysis, multivariate averaging for integral assessment, and rank correlation to examine relationships between ratings.The proposed author’s approach to a comprehensive assessment of regional market conditions is based on the multivariate mean method with data standardization by range. This allowed for the creation of an integral regional rating, clearly identifying leaders and outsiders in market development dynamics. Statistical analysis, conducted using Statistica software, revealed significant correlations between investment flows and socio-economic indicators. Particular attention was paid to investigating the relationship between economic ratings and the environmental status of regions, which showed a moderate inverse correlation. This indicates an existing contradiction between economic activity and environmental balance, emphasizing the importance of integrating ecological aspects into development strategies.Based on the results obtained, practical recommendations were developed to improve regional investment policy. These include increasing the targeting of funding, strengthening analytical monitoring of investment effectiveness, and diversifying funding sources to maximize positive impact. The study’s findings provide a valuable foundation for strategic regional development planning, especially under budget constraints, and contribute to achieving balanced and sustainable growth.